2010
DOI: 10.1007/s00056-010-9926-x
|View full text |Cite
|
Sign up to set email alerts
|

3D Soft Tissue Analysis – Part 1: Sagittal Parameters

Abstract: 3D soft tissue analysis provides additional information on the sagittal position of the jaw bases and on intermaxillary sagittal relations. Further studies are needed to integrate 3D soft tissue analysis in future treatment planning and assessment as a supportive diagnostic tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
1
13

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 34 publications
2
26
1
13
Order By: Relevance
“…The advantages of this method are the lack of motion artifacts because of the short imaging time, high color resolution, and the opportunity for administration without harming patients for repeated analyses, quick configuration, imaging via advanced software, ease of archiving, and 3D storage of patient images. 15,16 When 3D stereophotogrammetry devices become affordable and easily available, the method could become a routine procedure in orthodontic practice. Therefore, the present study aimed to compare three measurement methods and evaluate the accuracy of 3D stereophotogrammetry (3dMDflex System, 3dMD, Atlanta, Ga) by comparing it with direct anthropometry.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of this method are the lack of motion artifacts because of the short imaging time, high color resolution, and the opportunity for administration without harming patients for repeated analyses, quick configuration, imaging via advanced software, ease of archiving, and 3D storage of patient images. 15,16 When 3D stereophotogrammetry devices become affordable and easily available, the method could become a routine procedure in orthodontic practice. Therefore, the present study aimed to compare three measurement methods and evaluate the accuracy of 3D stereophotogrammetry (3dMDflex System, 3dMD, Atlanta, Ga) by comparing it with direct anthropometry.…”
Section: Introductionmentioning
confidence: 99%
“…However, no routinely-used 3D soft tissue analyses exist thus far because of the lack of 3D mean values for the facial soft tissues. In our previous study [22], we calculated sagittal 3D mean values for the facial tissue and examined their reliability and correlation with cephalometric values.…”
mentioning
confidence: 99%
“…Plastik ve alçı modellerin lazer taraması çalışmalarında, antropometrik noktalar kullanıldığında, araştırmacılar üç eksende (x, y ve z) 0,6 mm veya 0,5 mm.lik varyasyon bildirmişlerdir (4,46,47). Ayrıca antropometrik ölçümler için lazer sistemlerinin kullanıldığı daha kapsamlı çalışmaların yarısında da güvenilir olmadığı bulunmuştur (1,5 mm.den fazla hata) (48).…”
Section: Structured Lightunclassified
“…In studies about laser scanning of plastic and plaster models, researchers reported O,6-mm or 0.5 mm discrepancy of localization in the three axis (x, y and z) when using anthropometric landmarks (4,46,47). However, more comprehensive studies using laser systems for anthropometric measurements reported that more than half of these were unreliable (errors higher than 1.5 mm) (48).…”
Section: Structured Lightmentioning
confidence: 99%